Impact of Teacher Professionalism in Educational Technology on Student Learning Engagement - Dewi Safitri; Robie Fanreza (International Journal of Multidisciplinary Research of Higher Education, 2026)
The rapid advancement of information technology in the digital era requires Islamic Education teachers to demonstrate professionalism that extends beyond pedagogical competence and subject mastery, encompassing the effective use of learning technologies. This study investigates how student engagement in one Islamic educational institution in Indonesia is influenced by the professionalism of Islamic Education teachers in utilizing educational technology. Employing a causal-associative design with a quantitative methodology, thirty eleventh-grade students were randomly selected as participants. Data were collected through a Likert-scale questionnaire and analyzed using IBM SPSS Statistics with simple linear regression. Findings reveal a positive correlation (R = 0.305) between teacher professionalism in technology-based learning and student engagement. However, the contribution of teacher professionalism was modest (R² = 0.093), and the t-test indicated non-significance (p = 0.101 > 0.05). These results suggest that student engagement is not significantly affected by teachers’ digital competence, although the integration of educational technology remains essential for fostering interactive and participatory learning environments.